2005
DOI: 10.1002/ajmg.b.30152
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the gamma‐amino‐butyric acid type B receptor 1 (GABBR1) gene as a susceptibility factor in obsessive‐compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a well-recognized severe neuropsychiatric illness. Genetic factors are believed to be important etiologically. Although historically genetic testing has focused on the serotonergic and dopaminergic systems, there is increasing evidence that the major inhibitory neurotransmitter, gamma-aminobutyric acid (GABA), may also be functionally involved. Furthermore the GABA type B receptor 1 (GABBR1) gene has been localized to chromosome 6p21.3 region, which has shown linkage to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 28 publications
4
33
0
1
Order By: Relevance
“…As described above, such deficits are consistent with proposed mechanisms of OCD pathogenesis (Rosenberg and Keshavan 1998). The observed deficits in GABA B receptor-mediated inhibition are consistent with a study implicating the GABA B receptor 1 (GABBR1) gene in susceptibility gene to OCD (Zai et al, 2005). Additionally, our findings of increased ICF in OCD are in line with a wellreplicated finding of association between the neuronal glutamate transporter gene SLC1A1 and OCD (Arnold et al, 2006;Dickel et al, 2006;Liang et al, 2008;Stewart et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As described above, such deficits are consistent with proposed mechanisms of OCD pathogenesis (Rosenberg and Keshavan 1998). The observed deficits in GABA B receptor-mediated inhibition are consistent with a study implicating the GABA B receptor 1 (GABBR1) gene in susceptibility gene to OCD (Zai et al, 2005). Additionally, our findings of increased ICF in OCD are in line with a wellreplicated finding of association between the neuronal glutamate transporter gene SLC1A1 and OCD (Arnold et al, 2006;Dickel et al, 2006;Liang et al, 2008;Stewart et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Additional evidence supports the involvement of g-aminobutyric acid (GABA) and glutamatergic neurotransmission in OCD, including magnetic resonance spectroscopy studies, which suggest alterations in glutamate concentrations in the caudate in pediatric OCD (Rosenberg et al, 2000), and genetic studies implicating the glutamate transporter gene SLC1A1 (Arnold et al, 2006;Dickel et al, 2006), the glutamate N-Methyl-D-aspartate (NMDA) subunit receptor gene GRIN2B (Arnold et al, 2004;Dickel et al, 2006), as well as the GABA B receptor 1 (GABBR1) gene as susceptibility genes in OCD (Zai et al, 2005). Collectively the above represents compelling evidence that OCD is associated with deficient inhibition and excessive facilitation in the cortex.…”
Section: Introductionmentioning
confidence: 98%
“…Here we test the predictions of the model regarding selection processes that are supported by the left ventrolateral prefrontal cortex. We do so for the following reasons: (i) this region has been implicated in selecting among competing alternatives during language processing (6,(15)(16)(17)(18); (ii) this region shows altered activity in individuals who suffer from anxiety (particularly anxious apprehension, characterized by worry, and hereafter referred to as "anxiety" (19); and (iii) GABAergic function is reduced in individuals with anxiety (20)(21)(22)(23). Hence, our model provides a unified framework that can link these formerly disconnected observations.…”
mentioning
confidence: 99%
“…In this case, the results suggest that OCD is associated with deficient cortical silent period and excessive intracortical facilitation, regardless of medication state, reflecting abnormalities in GABA B and NMDA-mediated neurotransmission, which is consistent with the reults of several genetic studies of this disorder. [76][77][78][79][80][81] The authors suggested that differences between their results and those previously published could be owing to the greater number of unmedicated patients and elevated symptom severity in their sample or to the different stimulation intensities used to elicit measures. The discrepant findings in the limited number of studies highlight the need for further research to better characterize the potential abnormalities seen in patients with OCD.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 79%